Differences in Elementary School Students' Resilience Levels Based on Types of Extracurricular Activities - Myrna Apriany Lestari; M. Solehuddin; Yusi Riksa Yustiana; Ipah Saripah (MASI Mandiri Edukasi, 2026)
Elementary school students face increasing psychosocial and academic pressures, yet the role of extracurricular activities in shaping their resilience remains underexplored, particularly in the Indonesian primary education context. This study aims to analyze differences in resilience levels among elementary school students based on the types of extracurricular activities they participate in. A quantitative cross-sectional survey design was employed involving 114 fourth-to-sixth-grade students from six private elementary schools in Kuningan Regency, selected through stratified random sampling. Data were collected using a resilience questionnaire grounded in seven adaptive skill aspects and analyzed using descriptive statistics, cross-tabulations, Pearson’s Chi-Square test, and Monte Carlo simulation, with relationship strength measured using Cramér’s V coefficient. Results showed that the majority of students fell in the moderate resilience category, but significant differences existed across extracurricular activity types. Science and sports activities showed a greater proportion of high resilience compared to arts, religious, English, and scouting activities. The difference was statistically significant (p < 0.05) with a medium-to-large effect size (Cramér’s V = 0.416). These findings confirm that not all extracurricular activities contribute equally to resilience development. This research enriches Positive Youth Development studies by providing comparative quantitative evidence in Indonesian primary education and highlights the importance of designing evidence-based extracurricular programs that integrate social-emotional skills development.